(untitled) (Journal of Health Sciences, 2023)
Introduction: Knee osteoarthritis (OA) develops gradually and causes pain, a decrease in range of motion, muscle mass, and strength and leads to a decrease in physical activity and a poor quality of life for the patient. The aim of this study was to investigate the effects of different physiotherapy programs on pain intensity, range of motion, and quality of life in people with knee OA. Methods: The study was designed as a prospective, experimental, and randomized trial. Sixty subjects of both sexes and all ages with OA of the knee were enrolled in the study. In the studied Group I (n = 30), in addition to the standard protocol, high induction electromagnetic stimulation was applied using a Salus Talent device with a strength of 3 T and a frequency of up to 50 Hz for 10 min. In the test Group II (n = 30), in addition to the standard protocol, high-intensity laser therapy (HILT) with a power of 5 J was applied with the help of the Ilux Yag 1064 device for 7 min. The therapy protocol for both test groups lasted 8 weeks, with subjects treated once a week. Results: Analysis of the mean scores on the VAS scale shows that in both groups, the lowest mean scores were recorded in the III measurement (4.35) and the highest in the I measurement (7.96). In all three measurements, there was a difference in the extent of mobility of internal rotation in the form of a higher average range of motion in the test group II, in which HILT was applied. Analysis of the mean scores on the knee injury and osteoarthritis outcome score quality of life scale showed that in both groups, the lowest mean scores were recorded at the first measurement (14.84), with the mean score increasing at the second (32.95) and third measurements (41.08). Conclusion: Both methods showed significant results in reducing pain intensity, improving knee mobility, activities of daily living, and quality of life in people with knee OA. The obtained data do not give preference to any method but indicate them as adequate physiotherapy protocols to improve the function and quality of life of people with knee OA.